LOOKING AT A PORTRAIT OF STUDENT ARGUMENTATION SKILLS ON THE CONCEPT OF INHERITANCE (21ST CENTURY SKILLS STUDY) - Miaturrohmah Miaturrohmah; Wirawan Fadly (INSECTA: Integrative Science Education and Teaching Activity Journal, 2020)
This research was conducted to obtain a picture of the level of argumentation skills of students in science learning. This research is a starting point to find out the level of 21st century skills that are very important students have, one of which is argumentation skills. The method used is a qualitative study with a survey design and unstructured interviews with a sample of class IX A students in one of the Ponorogo District Junior High Schools selected by cross sectional random sampling. The results showed that the average of students 'argumentation skills was 71.528, which meant the level of students' argumentation skills in learning science was still relatively low. The results of this study become a reference for further research to improve students' argumentation skills in learning science especially1 Tadris IPA, IAIN Ponorogo, Indonesia